2009
DOI: 10.4038/cmj.v51i2.1351
|View full text |Cite
|
Sign up to set email alerts
|

Coconut fats

Abstract: In many areas of Sri Lanka the coconut tree and its products have for centuries been an integral part of life, and it has come to be called the "Tree of life". However, in the last few decades, the relationship between coconut fats and health has been the subject of much debate and misinformation.Coconut fats account for 80% of the fat intake among Sri Lankans. Around 92% of these fats are saturated fats. This has lead to the belief that coconut fats are 'bad for health', particularly in relation to ischaemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…Coconut oil is the main cooking oil in Sri Lanka [32], however, other types of cooking oils are used in different communities. Our FFQ does not enable us to differentiate the types of cooking oil consumed which may have important health implications for NCDs.…”
Section: Resultsmentioning
confidence: 99%
“…Coconut oil is the main cooking oil in Sri Lanka [32], however, other types of cooking oils are used in different communities. Our FFQ does not enable us to differentiate the types of cooking oil consumed which may have important health implications for NCDs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the amount of fat, the type of fat is crucial for development of diet-related chronic diseases such as cardiovascular disease. Although, sub types of fat are not reported in this analysis, the main lipid source in Sri Lankan diet is coconut milk/oil which is high in saturated fatty acids [27]. Therefore, it is important to conduct further studies to explore the coconut consumption and associated cardiovascular disease risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have shown an association between dietary saturated fat content and hyperinsulinaemia [13] impaired glucose tolerance [14,15] and overt diabetes [16]. Groundnut oil contains 46 and 32% of mono unsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA), respectively Palm oil contains approximately 50 % of saturated and 50 % unsaturated fatty acids [17], whilst coconut oil is, a saturated fat which contains predominantly medium-chain saturated fatty acids with high antioxidant properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%